PENERAPAN METODE SUPPORT VECTOR MACHINE UNTUK ANALISIS SENTIMEN PADA ULASAN PELANGGAN HOTEL DI TRIPADVISOR - Willyanto Wijaya; Dyah Erny Herwindiati; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
Indonesia is an archipelagic country that has very beautiful nature, in addition to the natural beauty of cultural diversity is also one of the factors Indonesia has a tourist attraction. One of the effects of Indonesia's natural beauty and cultural diversity can be seen from the increase in hotel occupancy rates. This hotel analysis system design uses training data and test data from the tripadvisor website. Tripadvisor is a website that focuses on tourism. on tripadvisor there are a lot of services offered ranging from transportation, lodging, travel experiences, and restaurants. One of the useful features of tripadvisor is the review column, this review column can be used to do research. visitor reviews from the tripadvisor comments column can be used as a value. to visualize and see people's emotions how the services provided by the hotel to visitors. The research phase starts from scrapping data from the triapadvisor review column, preprocessing data, word weighting, SVM, and evaluation with a confusion matrix. The data taken from the review column is done by web scraping technique. This study uses data from 3000 reviews from 15 hotels. The results of the classification will then be evaluated with a confusion matrix. The highest accuracy result will be used as a model for classification. the classification results will be displayed in the form of detailed tables and diagrams that describe the percentage of sentiment classification results.